Finite Element Analysis of Heat and Mass Transfer Effects on Unsteady MHD Free Convection Flow past a Vertical Permeable Moving Plate with Radiation - Gundagani Murali (Institute of Advanced Engineering and Science, 2012)
The paper examined the radiation effect on unsteady MHD free convection heat and mass transfer flow on a viscous, incompressible, electrically conducting fluid past a vertical permeable moving plate with radiation. The non-linear partial differential equations governing the flow have been solved numerically using finite element method. Graphical results for velocity, temperature and concentration profiles have been obtained, to show the effects of different parameters entering in the problem. Such flow problems are important in many processes, in which there is combined heat and mass transfer with radiation. It has been observed that the velocity increase with the increase in the radiation parameter and there is a increase in temperature with the increase in the value of radiation parameter.Keywords: Heat and Mass transfer, MHD, Radiation, FEM